Chinese FDI to Ukraine in the context of road and belt initiative - Liliya UKRAYINETS (Eastern European Journal of Regional Studies, 2019)
China is the leader of economic development among the countries of the Asian region and given its strong economic expansion it is the key economic center of the Asian and Eurasian mega-regions. The empirical study shows that Chinese investors receive additional incentives to invest in Ukraine if there is a prior positive investment experience, increasing market potential, and openness and economic freedom. As Ukraine is generally perceived as a path to European markets, the signing of the Association Agreement with the EU is a positive factor. However, the readiness of investors from China to support corruption schemes in the Ukrainian economy arouses concern. Therefore, in order to enhance and improve the structure of investment flows from China to Ukraine, it is necessary to take a number of measures to overcome corruption. One of the main priorities of modern Ukrainian foreign policy is joining Belt and Path Initiative.